Mirror of the world - Roland, Margaret Mary, author.
1 online resource
Keywords: "In the late fifteenth century, the production of print editions of Claudius Ptolemy's second century Geography sparked one of the most significant intellectual developments of the era-the production of mathematically-based, north-oriented maps. The production of world maps in England, however, was notably absent during this 'Ptolemaic revival.' As a result, the impact of Ptolemy's text on English geographical thought has been obscured and minimalized, with scholars speculating a possible English indifference to or isolation from European geographic developments. Tracing English geographical thought through the material culture of literary and popular texts, this study provides evidence for the reception and transmission of Ptolemaic-based geography in England during a critical period of geographic innovation and synthesis, one that laid the foundation for modern geographical representation. With evidence from prose romance, book illustration, theatrical performance, cosmological ceilings, and almanacs, Mirror of the World proposes a new, interdisciplinary literary and cartographic history of the influence of Ptolemaic geography in England, one that reveals the lively integration of geographic concepts through narrative and non-cartographic visual forms"--